2016
DOI: 10.1093/inthealth/ihw014
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion services for patients with sickle cell disease in Nigeria

Abstract: Current efforts of Nigerian public hospitals to provide safe blood and CTT fall short of best practice. Provision of apheresis machines, improvement of voluntary non-remunerated donor drive, screening for red cell antigens and antibodies, and availability of iron chelators would significantly improve SCD care in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Unfortunately, our study shows that only about a third of the haematologists will definitely commence exchange blood transfusion on patients "at risk" or those who have already developed stroke. This is similar to the findings of the study by Diaku-Akinwunmi, et al [18] also done across several Nigerian health facilities [18]. This shows a poor acceptance of the practice of EBT in our environment which is most likely due to challenges in availability of safe blood for transfusion in this environment as observed by Ahmed and his colleagues in a study conducted in Northern Nigeria [19] and also the financial burden on the patients and their relatives.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, our study shows that only about a third of the haematologists will definitely commence exchange blood transfusion on patients "at risk" or those who have already developed stroke. This is similar to the findings of the study by Diaku-Akinwunmi, et al [18] also done across several Nigerian health facilities [18]. This shows a poor acceptance of the practice of EBT in our environment which is most likely due to challenges in availability of safe blood for transfusion in this environment as observed by Ahmed and his colleagues in a study conducted in Northern Nigeria [19] and also the financial burden on the patients and their relatives.…”
Section: Discussionsupporting
confidence: 88%
“…Globally, about 312,000 neonates are born with SCA annually and 75% of these births occur in Africa . Nigeria has the highest burden of SCA in the world . SCA is characterized by heterogeneous clinical phenotypes, and genetic modifiers play roles in the clinical presentation of the disease …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Available evidence suggests that chronic blood transfusion therapy and automated RBC exchange are poorly available for SCD care in Nigeria. 18,19 In Nigeria, local studies have suggested o R i g i n a l R e p o R t Immune erythrocyte antibodies in adult patients with sickle cell disease and blood donors in Lagos, Nigeria: a comparative study A.S. Adewoyin, O.A. Daramola, A.A. Ogbenna, and T.A.…”
mentioning
confidence: 99%